Interaction between Practice Distribution and VO₂max in Improving Technical Skills of Junior Badminton Players - Mustofa, Hanafi; Sumintarsih, Sumintarsih; Saptono, Tri; Indriharta, Lilik; Saleh, R. Agung Purwandono (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2026)
This study examined the effects of massed and distributed practice, VO₂max levels, and their interaction on the improvement of basic badminton technical skills, including serve, clear, drop-shot, and smash accuracy. An experimental method with a 2 × 2 factorial design was used. The sample consisted of 24 athletes from PB Taruna Sleman, Yogyakarta, selected through purposive random sampling. Data were analyzed using two-way ANOVA after meeting normality (Liliefors) and homogeneity (Bartlett) assumptions at a 0.05 significance level. The results showed a significant effect of practice method on technical skill improvement, F(1.20) = 7.206, p < 0.05. Athletes with high VO₂max demonstrated greater improvement than those with low VO₂max, F(1.20) = 10.693, p < 0.05. A significant interaction effect was also found between training method and VO₂max, F(1.20) = 78.039, p < 0.05, with a large effect size (Partial η² ≈ 0.79). Descriptive findings indicated that athletes with high VO₂max achieved the greatest improvement under massed practice (ΔM = 39.83), while those with low VO₂max improved more under distributed practice (ΔM = 29.67). These findings indicate that training effectiveness depends on athletes’ aerobic capacity. Coaches should align training structure with physiological characteristics, where athletes with high VO₂max can tolerate denser practice, while those with lower VO₂max benefit more from distributed practice to maintain performance quality.